The risk premium in commodity futures pricing : from Keynes' (1930) theory of normal backwardation to Dusak's (1973) futures capital asset pricing model : a literature review and an empirical study of risk premia in precious metals futures - Dagan, Liat (School of Management Studies, 2014)
Includes bibliographical references (leaves 128-135).